Effects of the Na+/H+ Ion Exchanger on Susceptibility to COVID-19 and the Course of the Disease - Cumhur Cure, Medine; Cure, Erkan (Journal of the Renin-Angiotensin-Aldosterone System, 2021)
The Na+/H+ ion exchanger (NHE) pumps Na+ inward the cell and H+ ion outside the cell. NHE activity increases in response to a decrease in intracellular pH, and it maintains intracellular pH in a narrow range. Patients with obesity, diabetes, and hypertension and the elderly are prone to severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) infection. The angiotensin II (Ang II) level is high in chronic diseases such as diabetes, hypertension, and obesity. Ang II is the main stimulator of NHE, and an increased Ang II level causes prolonged NHE activation in these patients. The long-term increase in NHE activity causes H+ ions to leave the cell in patients with diabetes, hypertension, and obesity. Increasing H+ ions outside the cell lead to an increase in oxidative stress and reactive oxygen species. H+ ion flows into the cell due to the increased oxidative stress. This vicious circle causes intracellular pH to drop. Although NHE is activated when intracellular pH decreases, there is prolonged NHE activation in chronic diseases such as aforementioned. Novel coronavirus disease 2019 (COVID-19) progression may be more severe and mortal in these patients. SARS-CoV-2 readily invades the cell at low intracellular pH and causes infection. The renin-angiotensin system and NHE play a vital role in regulating intracellular pH. The reduction of NHE activity or its prolonged activation may cause susceptibility to SARS-CoV-2 infection by lowering intracellular pH in patients with diabetes, hypertension, and obesity. Prolonged NHE activation in these patients with COVID-19 may worsen the course of the disease. Scientists continue to investigate the mechanism of the disease and the factors that affect its clinical progression.